The dorsal hippocampus is required for the formation of long‐term duration memories in rats. (21st June 2021) - Hata, Toshimichi; Yamashita, Tatsuya; Kamada, Taisuke
Abstract: Interval timing—the perception of durations mainly in seconds or minutes—is a ubiquitous behavior in organisms. Animal studies have suggested that the hippocampus plays an essential role in duration memory; however, the memory processes involved are unclear. To clarify the role of the dorsal hippocampus in the acquisition of long‐term duration memories, we adapted the "time‐shift paradigm" to a peak‐interval procedure. After a sufficient number of training with an initial target duration (20 s), the rats underwent "shift sessions" with a new target duration (40 s) under a muscimol (0.5 µg per side) infusion into the bilateral dorsal hippocampus. The memory of the new target duration was then tested in drug‐free "probe sessions, " including trials in which no lever presses were reinforced. In the probe sessions, the mean response rate distribution of the muscimol group was located leftward to the control group, but these two response rate distributions were superimposed on the standardized time axis, suggesting a scalar property. In the session‐by‐session analysis, the mean peak time (an index of timing accuracy) of the muscimol group was lower than that of the control group in the probe sessions, but not in the shift sessions. These findings suggest that the dorsal hippocampus is required for the formation of long‐term duration memories within the range of interval timing. Abstract : After acquisition of a peak interval 20‐s procedure (d), the target time was shifted to 40‐s with or without intra‐dorsal hippocampal injection of muscimol (e, shift sessions). The peak times, the time at which the response rate was the maximum, of both groups were similar to each other in the shift sessions, whereas that of the muscimol group was lower than that of the control group in the probe sessions, including only trials in which no responses were reinforced (f).